Comparative Study of Pomegranate (Punica Granatum) Peel and Banana (Musa Paradisiaca L.) Peel Extracts as Natural Preservative and its Antioxidant Effect on Homemade Cake - Zulkapli, Nur Hidayah; Nor Faizah Razali (Progress in Engineering Application and Technology, 2025)
This study explores the potential of pomegranate (Punica granatum) peel and banana (Musa paradisiaca L.) peel extracts as natural preservatives, emphasizing their antioxidant properties and food preservation effects. Fruit peel, often considered waste, is rich in bioactive compounds like phenolics, making them viable alternatives to synthetic preservatives. This study aimed to extract and compare the total phenolic content (TPC), antioxidant activity, and antimicrobial effects of these peels using ultrasonic-assisted extraction (UAE). This study also aimed to evaluate the function of antimicrobial activity of synthetic preservatives, pomegranate peel and banana peel as natural preservatives on homemade cake. The TPC and antioxidant activity were measured using the Folin-Ciocalteu reagent and DPPH radical scavenging assays, while antimicrobial activity was assessed via the disc diffusion method. Pomegranate peels demonstrated superior TPC (2.669 mg GAE/g) and antioxidant activity (41.51% inhibition) compared to banana peels (1.925 mg GAE/g, 23.67% inhibition). Antimicrobial tests using the disc diffusion method revealed limitations in microbial inhibition under the experimental conditions. Application of the extracts to homemade cakes demonstrated the potential of pomegranate peel to extend shelf life up to 14 days without mold formation, outperforming banana peel and synthetic preservative BHA. The findings suggest that pomegranate peel, enriched with phenolic compounds, serves as a promising natural alternative for synthetic food preservatives, aligning with consumer demand for safer and eco-friendly options.